2015
DOI: 10.1586/14737140.2015.1092874
|View full text |Cite
|
Sign up to set email alerts
|

The roles of CD147 in the progression of gliomas

Abstract: Gliomas are characterized by their invasiveness, angiogenesis, glycolysis and poor prognosis. Determining how to inhibit angiogenesis and glycolysis and induce cell death in gliomas is essential to the development of an effective therapy. CD147, a highly glycosylated transmembrane glycoprotein with two Ig-like extracellular domains that belongs to the immunoglobulin superfamily, plays an important role in the regulation of tumor invasiveness, angiogenesis and glycolysis by inducing the secretion of matrix meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 97 publications
0
12
0
1
Order By: Relevance
“…A number of studies have demonstrated that CD147 serves an important role in glioma (15,27). The results of the present study also proved that CD147 was able to affect the development of glioma cells; knockdown of CD147 inhibited glioma cell growth, whereas CD147 overexpression enhanced cell growth in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that CD147 serves an important role in glioma (15,27). The results of the present study also proved that CD147 was able to affect the development of glioma cells; knockdown of CD147 inhibited glioma cell growth, whereas CD147 overexpression enhanced cell growth in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…N ‐acetylglucosaminyltransferase (GnT)‐V is a key glycosyltransferase that regulates the formation of β1,6‐Glc N Ac ( N ‐acetylglucosamine) branches during N‐glycosylation, which modulates the conversion of LG‐EMMPRIN to HG‐EMMPRIN . The glycosylation of EMMPRIN is of great importance in various physiological processes and pathological progression, such as human parturition, atherosclerotic lesions, inflammatory activity, tumor metastasis and chemoresistance . Furthermore, in the tumor microenvironment, EMMPRIN on tumor cells stimulates the expression of several types of MMPs through crosstalk with fibroblasts .…”
Section: Introductionmentioning
confidence: 99%
“…EMMPRIN has been demonstrated to be associated with the degree of malignancy, metastasis and prognosis of different types of cancer ( 35 , 36 ). The upregulation of EMMPRIN has also been described as a biomarker for a poor prognosis in patients with glioma ( 37 ). Sameshima et al ( 38 ) revealed that EMMPRIN was only expressed by the vascular endothelium in normal brain tissues, but was distributed throughout the cell membrane and cytoplasm in glioma tissues.…”
Section: Discussionmentioning
confidence: 99%